Facial emotion detection using Guided Particle Swarm Optimization (GPSO) - Bashir, Mohammed Ghandi; Nagarajan, R.; Hazry, Desa (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.